2020
DOI: 10.1016/j.enconman.2020.113428
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic assessment and techno-economic analysis of a liquid indium-based chemical looping system for biomass gasification

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 37 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…2. Sarafraz and Christo [28] performed thermodynamic analysis on the proposed chemical looping gasification system based on liquid metal oxide carrier (CLG-LMOC) and subsequently evaluated the economic viability of the process based on the levelized cost of energy (LCOE).…”
Section: Techno-economic Evaluation Models Without Optimizationmentioning
confidence: 99%
“…2. Sarafraz and Christo [28] performed thermodynamic analysis on the proposed chemical looping gasification system based on liquid metal oxide carrier (CLG-LMOC) and subsequently evaluated the economic viability of the process based on the levelized cost of energy (LCOE).…”
Section: Techno-economic Evaluation Models Without Optimizationmentioning
confidence: 99%
“…In the following work, the improved automatic disturbance rejection control is applied to the continuous reactor of the production to improve the stability, productivity, anti-interference, and energy efficiency of the continuous reactor and to alleviate the sludge environmental problems caused by the paper mill. Additionally, the internal circulation reactor used for integrated CO 2 capture and power generation [31] and the reactor in the liquid indium-based chemical circulation system based on biomass gasification [32], respectively, will introduce improved automatic disturbance rejection control to further reduce the energy loss involved in the capture of carbon dioxide from the conversion of hydrocarbon and to maintain the temperature stability to achieve the optimum performance.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…In addition to solving these operational challenges, the economic and environmental impact of CLG must be understood to facilitate its transition to an industrial scale. Only a few studies examined the technoeconomic aspects of biomass CLG and showed that the technology is outperforming several existing processes for power generation [26,27] and methanol production [28]. For power generation, Mohamed et al [27] performed a technoeconomic analysis for a potential plant, with a capacity of 650 MW using wood pellets as biomass feedstock and hematite as oxygen carrier.…”
Section: Introductionmentioning
confidence: 99%